Russia Lost or found (Edita, 2009)
The aim of this book is to illuminate the persistent patterns and future trajectories of developments in Russia and their relevance to Europe. It elaborates the concepts and practices of Russia power, society and the Russia idea, and refects on the legacies of the different layers of historical experience of today's Russia. The contributions to this work offer an analytic take on the key aspects of Russia's identity and its future role as a unique European state an increasingly turbulent world.